The Interactive Construction of Biological Individuality Through Biotic Entrenchment - Hernández, Isaac; Vecchi, Davide (Frontiers in Psychology, 2019)
In this paper we propose to critically evaluate whether a closure of constraints interpretation can make sense of biotic entrenchment, the process of assimilation and functional integration of environmental elements of biotic origin in development and, eventually, evolution. In order to achieve the aims of our analysis, we shall focus on multi-species partnerships, biological systems characterised by ontogenetic dependencies of various strength between the partners. Our main research question is to tackle the foundational problem posed by the dynamics of biotic entrenchment characterising multi-species partnerships for the closure of constraints interpretation, namely, to understand for which biological system (i.e., the partners taken individually or the partnership as the encompassing system) closure of constraints is realised. Through the analysis of significant illustrative examples, we shall progressively refine the closure thesis and articulate an answer to our main research question. We shall also propose that biotic entrenchment provides a chief example of the phenomenon of interactive and horizontal construction of biological individuality and inter-identity.